Using flow cytometry to follow the apoptotic cascade - Ormerod, M.G. (Redox report : communications in free radical research, 2001)
Flow cytometry has been extensively used to follow the apoptotic cascade and to enumerate apoptotic cells, both in cell cultures and, to a lesser extent, in tissue biopsies. An overview of the apoptotic cascade and how flow cytometric measurements can be used to observe the different elements of this process is presented.